Analisis Polemik Anggaran Pengadaan Baju Dinas DPRD Kota Tangerang Tahun 2021 - Sahala, Priyanto Renaldo; Noak, Piers Andreas; Erviantono, Tedi (Lenggogeni Data Publishing, 2024)
This research aims to analyze the polemic that occurred regarding the budget for the procurement of official clothing for the Tangerang City Regional People's Representative Council (DPRD) in 2021. Procurement of official clothing is an important part of the budget of government institutions, and controversy sometimes arises regarding transparency, fairness and accountability in its management. . The analytical method used involves documentation studies, interviews, and content analysis from various sources including official reports and media news. The findings of this research identify various issues such as the auction process, product quality, costs, and public perceptions of transparency and accountability in budget use. The implications of this analysis provide a clearer picture of the aspects that need to be improved in the management of the Tangerang City DPRD official clothing procurement budget to increase efficiency, effectiveness and integrity in the use of public funds.